(untitled) (World Marxist Review, 2026)
This paper develops a Marxist political economy analysis of Bulgaria's path toward Eurozone accession, situating monetary integration within the broader dynamics of post-socialist capitalist transformation. It argues that Euro adoption should not be understood as a neutral or technocratic policy but as a hegemonic class project that consolidates dependent accumulation, stabilizes domestic and transnational capitalist interests, and reproduces Bulgaria's semi-peripheral position in the European division of labour. The analysis traces the historical trajectory from state socialism to neoliberal restructuring, highlighting the roles of privatization, foreign capital penetration, and the currency-board regime in shaping accumulation strategies and class relations. Euro accession formalizes monetary and fiscal discipline, depoliticizes macroeconomic governance, and reinforces wage and labour constraints, thereby embedding Bulgaria further within a dependent and low-wage accumulation model. By bridging Marxist analyses of the Euro, post-socialist transformation, and peripheral capitalism, the paper contributes a theoretical framework for understanding Eurozone enlargement as a structural mechanism of capitalist consolidation rather than economic convergence.